From art to health action: lessons from a community-based, culturally tailored arts-meets-health educational campaign in Hispanic communities - Thomas J. Urich; Woori Lee; Justine Po; Arthur Bookstein; Rosa Barahona; Lourdes Baezconde-Garbanati (Frontiers Media S.A., 2024)
IntroductionRobust digital and community-led approaches are needed to combat health misinformation, as highlighted by the COVID-19 pandemic. Such gaps in public health outreach, compounded by systemic health barriers, contributed to higher rates of COVID-19 infection, mortality, and mental health effects among Hispanics during the peak of the pandemic. Thus, we conducted a community-based art-meets-health intervention [Stay Connected Los Angeles (SCLA)] to address the impacts of the COVID-19 pandemic in Hispanic communities.MethodsLed by local artists in collaboration with public health specialists and community members, SCLA used multimedia to promote infection mitigation behaviors and psychological well-being among the 120,000 residents of Eastern Los Angeles. Campaign materials were designed with input from community representatives and included digital media, large-scale murals, and comic-book style pieces. Two semi-structured focus groups (one in English and another in Spanish) were conducted to solicit participants' views on attributes of the campaign. Independent coders analyzed transcripts and applied thematic analysis to summarize key learnings regarding central health and mitigation messages, media modalities, how health information would be communicated, and the ideal spokespersons for delivering health-related messages.ResultsFocus group participants emphasized the effectiveness of social media, GIFs, and references to popular media. Further, youth involvement in the creative process was deemed to be important. Participants highlighted the need for clarity in public health messaging and adaptation of visual campaigns to the preferences of diverse age groups through different art styles. Finally, community leaders were found to be critical health information sources.DiscussionAs a model of a culturally tailored arts-meets health public education campaign, SCLA yielded valuable information on how to structure future public health messaging and media to create a meaningful improvement in health knowledge, mental well-being, and compliance with mitigation behaviors in communities that are often overlooked. Contributions from local artists can heighten appeal and acceptability of messages.